Nitrogen management sensor optimization, yield, economics, and nitrogen use efficiency of different wheat cultivars under varying nitrogen levels - Kumar, Bipin; Shaloo,; Bisht, Himani; Meena, M. C.; Dey, Abir; Dass, Anchal; Paramesh, Venkatesh; Babu, Subhash; Upadhyay, Pravin Kumar; Prajapati, Vijay Kumar; Chandanshive, Aniket; Suna, Truptimayee; et al. (Frontiers in Sustainable Food Systems, 2023)
Excessive application of nitrogen (N) in wheat cultivation results in substantial decreases in yield and limited economic gains, leading to adverse environmental consequences. In this study, the main objective is to assess and optimize the values of different N-assessing tools at varying levels of N for three wheat cultivars. Three non-destructive sensing devices: Leaf color chart (LCC), soil plant analyzer development (SPAD), and Green Seeker, were optimized at three levels of N (0, 90, 120, and 150 kg N ha−1) in three wheat cultivars, HD 2967, HD 3059, and HD 3086. The results indicated that at 60 days after sowing (DAS), the optimum values for LCC, SPAD, and GreenSeeker were 4.17, 0.62, and 44.2, respectively. These values were observed at the flag leaf stage, where they measured 4.12, 0.60, and 43.8, respectively, and this could be achieved at 120 kg N ha−1 with a grain yield of 4.87 t ha−1. At 120 kg N ha−1, considerably better gross return (Rs. 97,444.4), net income (Rs. 66,681.4), and B:C ratio (2.2) were obtained. The highest agronomic efficiency of N (21.2%) was recorded at 120 kg N ha−1, while the N uptake and recovery (129 kg ha−1 and 59.2 %) were significantly higher, recorded at 150 kg N ha−1. We can conclude that optimized values of these sensors at different doses of N would provide better guidance for precision N management that may reduce the input cost, maximize return, and minimize N losses in wheat.